Hubungan Usia, Pola Konsumsi Protein dan Lemak dengan Obesitas Sentral pada Wanita Usia Subur : Correlation between Protein and Fat Consumption Patterns with Central Obesity in Women of Childbearing Age - Ambar Wati, Desti; Ary Saputri, Retno (Svasta Harena: Jurnal Ilmiah Gizi, 2024)
Background: Age and a diet high in protein and fat are factors that cause central obesity. The high prevalence of central obesity, especially in women of childbearing age, can contribute to metabolic diseases..Purpose: This study aims to analyze the relationship between age, protein and fat consumption patterns and central obesity in women of childbearing age (WUS) in the working area of the Talang Padang Community Health Center. MethodsThe design of this research was cross-sectional with a purposive sampling technique and a sample of 35 WUS were obtained who had an abdominal circumference of >80 cm. The research was conducted in January 2023. Age data was obtained by interviews using a respondent identity questionnaire, data on protein and fat consumption patterns was obtained by interviews using the Quantitative Food Frequency Questionnaire (SQ-FFQ), and central obesity data was obtained by measuring abdominal circumference using Medline. Data analysis used the Spearman Rank statistical test because it was not normally distributed. Results: Based on the results of statistical analysis, it was concluded that there was a relationship between age and central obesity (p value = 0.05). However, there is no significant relationship between protein consumption patterns (p value=0.34) and fat consumption patterns (p value=0.47) with central obesity in women of childbearing age (WUS) in the UPTD working area of the Talang Padang Community Health Center. Conclusion: The age variable is significantly related to central obesity in women of childbearing age.